Transforming for a better future - Abd Razak, Dzulkifli (2010)
IDEA: Malaysia Inventors’ Challenge made its debut with the first of 10 episodes appearing on TV3 at 7pm last week. This first of its kind of reality show in Malaysia was launched on Aug 13 at the Theatrette, Sri Pentas, Petaling Jaya by Deputy Minister of Science, Technology and Innovation Fadillah Yusof. The programme is sponsored by Proton, organised by SIRIM and supported by the Malaysian Productivity Board (MPC). The hosts for the show are Daphne Iking and Mejar Dr Faiz Khaleed.